2020
DOI: 10.1186/s12967-020-02472-z
|View full text |Cite
|
Sign up to set email alerts
|

A consideration of publication-derived immune-related associations in Coronavirus and related lung damaging diseases

Abstract: Background The severe acute respiratory syndrome virus SARS-CoV-2, a close relative of the SARS-CoV virus, is the cause of the recent COVID-19 pandemic affecting, to date, over 14 million individuals across the globe and demonstrating relatively high rates of infection and mortality. A third virus, the H5N1, responsible for avian influenza, has caused infection with some clinical similarities to those in COVID-19 infections. Cytokines, small proteins that modulate immune responses, have been direc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 28 publications
(26 reference statements)
0
3
0
Order By: Relevance
“…Inconsistent results were reported for chronic obstructive pulmonary disease and asthma as risk factors. 6,24,27 Two studies analyzing the correlation between ABO blood group and clinical outcome suggested that blood group A individuals as well as those with rhesus antigen positivity were more susceptible to SARS-CoV-2 infection compared with blood groups O or AB. 28,29 However, blood groups are not among the risk factors for either disease severity or complications.…”
Section: Clinical Characteristics and Risk Factors Associated With Sa...mentioning
confidence: 99%
“…Inconsistent results were reported for chronic obstructive pulmonary disease and asthma as risk factors. 6,24,27 Two studies analyzing the correlation between ABO blood group and clinical outcome suggested that blood group A individuals as well as those with rhesus antigen positivity were more susceptible to SARS-CoV-2 infection compared with blood groups O or AB. 28,29 However, blood groups are not among the risk factors for either disease severity or complications.…”
Section: Clinical Characteristics and Risk Factors Associated With Sa...mentioning
confidence: 99%
“…We have previously described an approach ( 7 , 8 ) that can mine PubMed records for associations and linkages between different, formally defined, concepts and fields using Medical Subject Heading (MeSH) terms. This quantitative approach is a rapid tool that can be used iteratively to search for trends.…”
Section: Methodsmentioning
confidence: 99%
“…Prior studies on the biomarkers associated with SARS-CoV-2 immune response and morbidity include interferon-gamma (IFN-γ), interferon-beta (IFN-β), and interleukin-8 (IL-8) [12]. Other previous research on immune parameters associated with SARS-CoV-2 severity and prognosis have involved interleukin-1 beta (IL-1β) and interleukin-6 (IL-6).…”
Section: Introductionmentioning
confidence: 99%